Role of the whitefly maturation period on mosaic disease propagation in Jatropha curcas plant - Basir, Fahad Al (Frontiers in Applied Mathematics and Statistics, 2023)
Mosaic disease in Jatropha curcas plants is caused by begomoviruses carried by whitefly vectors, and only mature vectors can transmit the virus. In this paper, a mathematical model is developed for the dynamic analysis of the spread of mosaic disease in the Jatropha curcas plantation, accounting for the whitefly maturation period as a time delay factor. The existence conditions and stability of the equilibrium points have been studied with qualitative theory. The Basic reproduction number, R0 is determined to study the stability of the disease-free equilibrium with respect to it. Transcritical bifurcation of the disease-free equilibrium and Hopf bifurcation of the endemic equilibrium are also analyzed. Using numerical simulations, the analytical findings are verified and discussed the different dynamical behaviors of the system. In this research stabilising role of maturation delay has been established. That means when maturation time is large, disease will be transmitted when the infection rate is high.